Clinical Learning Outcomes in Midwifery Education: Evaluating the Effectiveness of Structured Clinical Instructor Guidance (IJORER : International Journal of Recent Educational Research, 2026)
Objective: This study aimed to evaluate the effectiveness of a structured clinical instructor guidance program on midwifery students' clinical learning outcomes and competency achievement. Method: A quasi-experimental design with pre-test and post-test control group was employed. The study involved 120 third-year midwifery students from two Indonesian institutions, randomly assigned to intervention (n=60) and control groups (n=60). The intervention group received a structured clinical instructor guidance program based on Training of Trainers (ToT) principles, including standardized mentoring protocols, competency assessment rubrics, and reflective practice sessions over 12 weeks. The control group continued with conventional clinical supervision. Data were collected using the Clinical Competency Assessment Tool (CCAT) and Clinical Learning Experience Questionnaire (CLEQ). Statistical analysis included independent t-tests, paired t-tests, and multiple regression to examine the intervention's effects. Results: The intervention group demonstrated significantly higher improvements in clinical competency scores compared to the control group (mean difference = 15.6 points, p < 0.001, Cohen's d = 1.24). Post-test scores showed 85% of intervention group students achieved "competent" level versus 45% in the control group. Regression analysis revealed that structured guidance accounted for 62% of variance in clinical competency (R² = 0.62, p < 0.001). Students in the intervention group also reported significantly higher satisfaction with clinical learning experiences (p < 0.01). Novelty: This study introduces and validates a structured clinical instructor guidance model specifically designed for midwifery education in resource-limited settings. It provides empirical evidence for integrating Training of Trainers (ToT) approaches into clinical supervision, addressing a critical gap in competency-based midwifery education. The developed assessment tools offer a standardized framework for evaluating clinical learning outcomes in health professional education.